An examination of skepticism: Maintaining audit quality under the pressure of audit fees - Afnisah, Anggi; Hasibuan, Khairul Amri (Indonesia Auditing Research Journal, 2026)
Audit quality remains a critical issue in maintaining the credibility of financial reporting, particularly amid economic pressures arising from audit fee arrangements between auditors and clients. While audit fees are expected to reflect audit effort and complexity, their direct influence on audit quality remains debatable. In this context, professional skepticism may serve as a key behavioral factor determining whether economic incentives enhance or undermine audit performance. This research examines the role of audit compensations in determining audit quality, with professional skepticism as a moderating variable among auditors at Public Accounting Firms in Medan. Using a quantitative causal associative design, data were gathered from 45 auditors via purposive sampling and analyzed with Partial Least Squares–Structural Equation Modeling (PLS-SEM). Findings indicate that audit fees do not have a significant direct effect on audit quality, whereas professional skepticism has a positive and significant effect. Moreover, professional skepticism significantly moderates the relationship between audit fees and audit quality, demonstrating a pure moderation effect. These results suggest audit quality is more strongly influenced by auditors’ professional attitudes than by economic factors alone.